DINAMIKA KOMPETENSI PERADILAN AGAMA DALAM MENGATASI SENGKETA EKONOMI SYARIAH : Fathor Rozy, Andhena Wisnu Wardana, Fatihul akmal Fardi Anshori, Hafshah - Rozy Fathor; Andhena Wisnu Wardana; Fatihul Akmal Fardi Anshori; Hafshah Hafshah (KASBANA, 2024)
Sharia Court is a legal venue to seek justice or settle civil disputes based on Islamic law, where it adjudicates, examines, and resolves civil cases at the first instance involving Muslim individuals, according to regulations derived from Sharia. According to Law No. 3 of 2006, Sharia Courts are authorized to adjudicate and resolve disputes related to Sharia economics, encompassing all business activities conducted in accordance with Sharia principles. The research methodology employed in this article is Normative legal research. The objective of this study is to analyze the general overview of Sharia economic disputes in Sharia Courts and to assess the capacity of Sharia Court judges in resolving Sharia economic cases. The findings of this research article indicate that Sharia economic disputes through litigation can be settled in Sharia Courts, thus requiring Sharia Court judges to comprehend and deepen their understanding of Sharia economics matters within their jurisdiction.